O discurso sobre os conceitos probabilísticos para a escola básica - Goulart, Amari (2007)
The object of our research was to analyze the official speech of the probability concepts in the Basic School and to verify if this speech gives to the teacher instruments to work with these concepts, so that the students can learn these concepts in a significative way. So we analyzed the PCN, PCN+, and the Curricular Orientations for Middle School and referred questions of probability on the ENEM tests from 1998 to 2007, by the Customary Organization of Yves Chevallard (1995), that gave us conditions to identify the objectives, suggestions of contents, methods of work and criteria of evaluation in official documents, and to identify the theoretician-technological tasks, techniques and speeches, present in the questions of the ENEM. The results had been compared with some research produced in the scope of the Mathematical Education that approaches the education and the learning of probability concepts. In general way, the analysis of the information gotten, allow us to conclude that the official documents didn t give aid to the teacher and that the ENEM, in certain way, is responsible for supplying these aiding elements